An Updated View on the Rck Invasin of Salmonella: Still Much to Discover - Mambu, Julien; Virlogeux-Payant, Isabelle; Holbert, Sébastien; Grépinet, Olivier; Velge, Philippe; Wiedemann, Agnès (Frontiers in Cellular and Infection Microbiology, 2017)
Salmonella is a facultative intracellular Gram-negative bacterium, responsible for a wide range of food- and water-borne diseases ranging from gastroenteritis to typhoid fever depending on hosts and serotypes. Salmonella thus represents a major threat to public health. A key step in Salmonella pathogenesis is the invasion of phagocytic and non-phagocytic host cells. To trigger its own internalization into non-phagocytic cells, Salmonella has developed different mechanisms, involving several invasion factors. For decades, it was accepted that Salmonella could only enter cells through a type three secretion system, called T3SS-1. Recent research has shown that this bacterium expresses outer membrane proteins, such as the Rck protein, which is able to induce Salmonella entry mechanism. Rck mimics natural host cell ligands and triggers engulfment of the bacterium by interacting with the epidermal growth factor receptor. Salmonella is thus able to use multiple entry pathways during the Salmonella infection process. However, it is unclear how and when Salmonella exploits the T3SS-1 and Rck entry mechanisms. As a series of reviews have focused on the T3SS-1, this review aims to describe the current knowledge and the limitations of our understanding of the Rck outer membrane protein. The regulatory cascade which controls Rck expression and the molecular mechanisms underlying Rck-mediated invasion into cells are summarized. The potential role of Rck-mediated invasion in Salmonella pathogenesis and the intracellular behavior of the bacteria following a Salmonella Rck-dependent entry are discussed.